2007
DOI: 10.1590/s0100-879x2006005000107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metabolic control on interferon-gamma and interleukin-10 production by peripheral blood mononuclear cells from type 1 and type 2 diabetic patients

Abstract: The objective of the present study was to evaluate the production of cytokines, interferon-γ (INF-γ) and interleukin-10 (IL-10), in cultures of peripheral blood mononuclear cells (PBMC) from type 1 and type 2 diabetic patients and to correlate it with inadequate and adequate metabolic control. We studied 11 type 1 and 13 type 2 diabetic patients and 21 healthy individuals divided into two groups (N = 11 and 10) paired by sex and age with type 1 and type 2 diabetic patients. The PBMC cultures were stimulated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…A previous study reported that IFN-γ and IL-10 production in diabetic peripheral blood mononuclear cells were associated with metabolic control. This result indicated that good metabolic control in diabetic patients would improve activation and maintenance of the immune response and decrease vulnerability to infection [37].…”
Section: Hba1c Levelsmentioning
confidence: 87%
“…A previous study reported that IFN-γ and IL-10 production in diabetic peripheral blood mononuclear cells were associated with metabolic control. This result indicated that good metabolic control in diabetic patients would improve activation and maintenance of the immune response and decrease vulnerability to infection [37].…”
Section: Hba1c Levelsmentioning
confidence: 87%
“…18 Although it was shown that impairment of polymorphonuclear phagocytosis and reduction in granulocyte phagocytic capacity in IDDM persons with inadequate metabolic control lead to an increase in susceptibility to infection, these abnormalities are reversible after insulin therapy. [19][20][21][22][23][24] In previous studies, increased proliferation capacity of IDDM T-lymphocytes 25 and a tendency toward increased tumor necrosis factor-α and interleukin-6, 26 as well as increased levels of interferon-γ levels, 27 after metabolic control were reported. Ten years after HB vaccination, 70% of our IDDM patients had anti-HBs levels of <10 IU/L.…”
Section: Discussionmentioning
confidence: 99%